A polyester film with low shrinkage, good adhesion and wear resistance and preparation method thereof

By introducing the core layer structure into the polyester film and directly adding scratch-resistant wear-resistant materials, the existing protective film is solved, and the existing protective film is easily peeled off on the coating layer, the double-pull film cannot be heat-sealed, poor covering properties and complex process, and the polyester film has been achieved with a low shrinkage, wear resistance and coating properties, and the process is simple and practical.

CN115593063BActive Publication Date: 2025-04-18HANGZHOU WENTAI PLASTICS CO LTD

Patent Information

Application Number
CN202211122510.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-15
Publication Date
2025-04-18
Estimated Expiration
2042-09-15

AI Technical Summary

Technical Problem

The existing protective film has problems such as easy peeling of the coating layer, inability to heat seal the double-pull film, poor coating properties and complex process, and it is difficult to meet the high requirements for low shrinkage, wear resistance and coating properties.

Method used

The core layer structure is introduced by multi-layer co-extrusion, and scratch-resistant materials are directly added to the surface layer film to form a low shrinkage and wear-resistant polyester film, achieving wear-resistant and scratch-resistant functions without coating treatment, and improving heat sealing and covering performance.

Benefits of technology

The low shrinkage, wear resistance and coverability of the polyester film are achieved, and the problems of peeling off the coating layer and heat sealing are avoided, and the process is simple and practical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115593063B_ABST
    Figure CN115593063B_ABST
Patent Text Reader

Abstract

The present invention relates to a polyester film with low shrinkage, good adhesion and wear resistance and a preparation method thereof. The polyester film comprises two surface layers and a core layer located between the two surface layers; the material of the surface layer is mainly composed of polybutylene terephthalate and a wear-resistant agent; the material of the core layer is mainly composed of a mixture of polycarbonate and polyethylene terephthalate-1,4-cyclohexanedimethanol. Preparation method: manufacturing surface layer pellets; manufacturing core layer pellets; extruding the melts separately and compounding them in a die head, and then subjecting them to shaping, cooling, pulling and annealing to obtain a polyester film. In the present invention, a core layer structure is introduced by a multi-layer co-extrusion method, and the film has wear-resistant and scratch-resistant functions after film formation, and no coating treatment is required; the core layer structure can achieve a low shrinkage rate and is easy to heat-seal; at the same time, the softening point of the introduced core layer is very low, so that the overall adhesion of the film is strong, and it has good adhesion performance to irregular concave and convex surfaces; the preparation method has a simple process and strong practicality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of film coating, and in particular to a polyester film with low shrinkage, good adhesion and wear resistance and a preparation method thereof. Background Art

[0002] At present, protective films are widely used in the fields of LCD panels, solar panels, high-end engraved copper plates, engraved aluminum plates, etc. Most of these protective films are coated with PET films with anti-scratch coatings, and some are coated with polypropylene films with anti-scratch coatings. These protective films all use biaxially stretched films to achieve low shrinkage performance, and use coating layers to achieve anti-scratch functions. However, these protective films generally have the following problems: 1. The coating layer is easy to peel off and transfer to the surface of the protected plate; 2. The biaxially stretched film cannot be heat-sealed; 3. The biaxially stretched film has poor adhesion to curved surfaces and irregular concave and convex surfaces; 4. The coating process requires special environmental protection equipment, which is not easy to implement. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a polyester film with low shrinkage, good adhesion and wear resistance and a preparation method thereof. A core layer structure is introduced in a multi-layer co-extrusion manner, and scratch-resistant and wear-resistant materials are directly added to the surface film, so that the film has wear-resistant and scratch-resistant functions after film formation, and no coating treatment is required. There is no coating on the surface, no worry about peeling, and no residual pollution. The introduced core layer structure can achieve a low shrinkage rate and is easy to heat seal. At the same time, the softening point of the introduced core layer is very low, so that the overall adhesion of the film is strong, and it can fully fit on uneven surfaces, especially uneven surfaces after carving, and has good adhesion to irregular surfaces. The preparation method has a simple process and strong practicality.

[0004] The technical solution adopted by the present invention to solve its technical problems is: a polyester film with low shrinkage, good adhesion and wear resistance, comprising two surface layers and a core layer located between the two surface layers; the material of the surface layer is mainly composed of polybutylene terephthalate and a wear-resistant agent; the material of the core layer is mainly composed of a mixture of polycarbonate and polyethylene terephthalate-1,4-cyclohexanedimethanol ester.

[0005] Furthermore, the surface layer material mainly consists of 80-99 parts of polybutylene terephthalate and 0.001-10 parts of anti-wear agent by mass.

[0006] Furthermore, the wear-resistant agent is one or a combination of tetrafluoroethylene powder and silicon dioxide powder.

[0007] Furthermore, the core layer material mainly consists of 10-90 parts by mass of polycarbonate and 10-90 parts by mass of polyethylene terephthalate-1,4-cyclohexanedimethanol.

[0008] Furthermore, thermoplastic polyester elastomer is added to the surface layer material.

[0009] A method for preparing a polyester film with low shrinkage, good adhesion and wear resistance, which is specifically carried out according to the following steps:

[0010] S1, polybutylene terephthalate, anti-wear agent and other additives are mixed in a high-speed mixer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain surface layer pellets;

[0011] S2, mixing polycarbonate, polyethylene terephthalate-1,4-cyclohexanedimethanol, and other additives in a high-speed mixer, and then melt-blending, extruding, and granulating through a twin-screw extruder to obtain core layer pellets;

[0012] S3. Prepare a three-layer co-extrusion extruder consisting of two extruders, add the surface layer pellets to the first extruder, add the core layer pellets to the second extruder, the extruded melt enters and is compounded in the die head, and the compounded multi-layer melt is shaped, cooled, pulled, and annealed to obtain a polyester film.

[0013] Furthermore, in step S1, the melt blending time of the twin-screw extruder is 2-10 min, the extrusion temperature is 190-240°C, and the screw speed is 15-80 r / min; in step S2, the melt blending time of the twin-screw extruder is 2-10 min, the extrusion temperature is 190-220°C, and the screw speed is 15-80 r / min.

[0014] Further, in step S3, the first extruder has a screw aspect ratio of 25-33, and comprises a barrel with 6 heating zones, and the barrel temperatures are respectively set to: 220-270°C in the first zone, 230-280°C in the second zone, 230-280°C in the third zone, 230-280°C in the fourth zone, 230-280°C in the fifth zone, and 230-280°C in the sixth zone;

[0015] Furthermore, in step S3, the second extruder has a screw aspect ratio of 25-33, and comprises a barrel with 6 heating zones, and the barrel temperatures are set to: 190-220°C in the first zone, 190-230°C in the second zone, 190-230°C in the third zone, 190-230°C in the fourth zone, 190-230°C in the fifth zone, and 190-230°C in the sixth zone.

[0016] Furthermore, in step S3, the die head is a single-channel intracavity composite die head, and the temperature is set to 220-280°C.

[0017] Advantages of the present invention: The present invention provides a polyester film with low shrinkage, good adhesion and wear resistance and a preparation method thereof, adopts a multi-layer co-extrusion method to introduce a core layer structure, and directly adds scratch-resistant and wear-resistant materials to the surface film, so that the film has wear-resistant and scratch-resistant functions after film formation, does not require coating treatment, has no coating on the surface, does not worry about peeling, and has no residual pollution; the introduced core layer structure can achieve a low shrinkage rate and is easy to heat seal; at the same time, the softening point of the introduced core layer is very low, so that the overall adhesion of the film is strong, and it can fully fit on uneven surfaces, especially uneven surfaces after carving, and has good adhesion performance on irregular surfaces; the preparation method has a simple process and strong practicality. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the structure of a polyester film with low shrinkage, good adhesion and wear resistance in an embodiment;

[0019] Among them, 100-surface layer, 200-core layer. DETAILED DESCRIPTION

[0020] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The embodiments are only used to explain the present invention and do not limit the protection scope of the present invention.

[0021] Example

[0022] Please refer to Figure 1 As shown, this embodiment provides a polyester film with low shrinkage, good adhesion and wear resistance, which includes at least two surface layers 100 and a core layer 200 located between the two surface layers; the material of the surface layer is mainly composed of polybutylene terephthalate (PBT) and a wear-resistant agent; the material of the core layer is mainly composed of a mixture of polycarbonate (PC) and polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG).

[0023] In the polyester film with low shrinkage, good adhesion and wear resistance of the present embodiment, the surface layer material is mainly composed of 80-99 parts of polybutylene terephthalate and 0.001-10 parts of wear-resistant agent by mass; the wear-resistant agent is one or a combination of tetrafluoroethylene powder and silicon dioxide powder; the surface layer contains an appropriate amount of tetrafluoroethylene powder and / or silicon dioxide powder, which can make the surface tension of the polyester film not higher than 32 dynes / cm and the surface hardness not lower than 2H; and achieve good anti-scratch and wear-resistant properties.

[0024] In the polyester film with low shrinkage, good adhesion and wear resistance of this embodiment, the surface layer material also contains other additives, including but not limited to antioxidants, anti-ultraviolet additives, lubricants and dispersants.

[0025] In the polyester film of this embodiment with low shrinkage, good adhesion and wear resistance, the surface layer material may further be added with an appropriate amount of thermoplastic elastomer (TPEE) to improve the heat sealing performance.

[0026] In the polyester film with low shrinkage, good adhesion and wear resistance of this embodiment, the core layer material is mainly composed of 10-90 parts of polycarbonate and 10-90 parts of polyethylene terephthalate-1,4-cyclohexanedimethanol ester by mass; the core layer contains a mixture of PC and PETG, which greatly improves the heat shrinkage problem of existing covering materials; PC and PETG are non-crystalline materials, and the product will not shrink due to crystallization after heating during the heat sealing and bonding process. At the same time, it has strong toughness and good deformability on products with uneven shapes to ensure that the film will not be damaged when coated; at the same time, the softening point of PETG is low (about 70°C), which is lower than the 100°C of general plastic heat sealing, so that the protective film can be accurately coated or bonded with the product at low temperature, reducing the operating temperature. For those products that are sensitive to high temperatures, the probability of damage due to heat sealing can be avoided, for example, the probability of failure of liquid crystal panels due to high temperature can be avoided.

[0027] In the polyester film with low shrinkage, good adhesion and wear resistance of this embodiment, the materials of the surface layer and the core layer are both polyester materials, which are naturally tightly combined without adding an adhesive layer or using an adhesive. The polyester film has a simple structure and no adhesive pollution.

[0028] This embodiment also provides a method for preparing a polyester film with low shrinkage, good adhesion and wear resistance, which is specifically carried out in the following steps:

[0029] S1, polybutylene terephthalate, anti-wear agent and other additives are mixed in a high-speed mixer, and then melt-blended, extruded, pulled, cooled and granulated by a twin-screw extruder to obtain surface layer pellets;

[0030] S2, polycarbonate, polyethylene terephthalate-1,4-cyclohexanedimethanol, and other additives are mixed in a high-speed mixer, and then melt-blended, extruded, and pulverized by a twin-screw extruder to obtain core layer pellets;

[0031] S3. Prepare a three-layer co-extrusion extruder consisting of two extruders, add the surface layer pellets to the first extruder, add the core layer pellets to the second extruder, the extruded melt enters and is compounded in the compound die head, and the compounded multi-layer melt is shaped, cooled, pulled, and annealed to obtain a polyester film.

[0032] In the preparation method of a polyester film with low shrinkage, good adhesion and wear resistance of the present embodiment, in step S1, the melt blending time of the twin-screw extruder is 2-10min, the extrusion temperature is 190-240°C, and the screw speed is 15-80r / min; after traction cooling granulation, it is dried at 100°C for 6h; in step S2, the melt blending time of the twin-screw extruder is 2-10min, the extrusion temperature is 190-220°C, and the screw speed is 15-80r / min; after traction cooling granulation, it is dried at 80°C for 12h.

[0033] In the preparation method of a polyester film with low shrinkage, good adhesion and wear resistance of the present embodiment, in step S3, the screw aspect ratio of the first extruder is 25-33, and it comprises 6 heating zone barrels, and the barrel temperatures are respectively set to: 220-270°C in the first zone, 230-280°C in the second zone, 230-280°C in the third zone, 230-280°C in the fourth zone, 230-280°C in the fifth zone, and 230-280°C in the sixth zone; in step S3, the screw aspect ratio of the second extruder is 25-33, and it comprises 6 heating zone barrels, and the barrel temperatures are respectively set to: 190-220°C in the first zone, 190-230°C in the second zone, 190-230°C in the third zone, 190-230°C in the fourth zone, 190-230°C in the fifth zone, and 190-230°C in the sixth zone.

[0034] In the method for preparing a polyester film with low shrinkage, good adhesion and wear resistance of this embodiment, in step S3, the casting die is a single-channel hanger-type casting die, and the temperature is set to 220-280°C.

[0035] In order to further demonstrate the effect of the present invention, the present invention will be further explained in conjunction with the following preparation examples; the following preparation examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0036] Manufacturing example

[0037] In the following multiple manufacturing examples, unless otherwise specified, the following configurations are used:

[0038] Surface layer: PBT, wear-resistant agent (silicon dioxide powder and / or tetrafluoroethylene powder), antioxidant, anti-ultraviolet additive, lubricant, dispersant.

[0039] Core layer: PC, PETG, antioxidant, anti-UV additive, compatibilizer.

[0040] Wear-resistant agent in the surface layer: tetrafluoroethylene powder can be produced by suspension method or cracking method, preferably tetrafluoroethylene powder with a particle size of 10μm-25μm produced by Germany's Sanye Technology; silica powder can be selected as fumed silica with a particle size distribution of 1μm-15μm.

[0041] The antioxidants in the surface layer and the core layer include, but are not limited to, one of antioxidant 1010, antioxidant 168, antioxidant 1098, or a combination of several of them.

[0042] The anti-ultraviolet additives in the surface layer and the core layer include, but are not limited to, one selected from UV531, UV326, UV329, and light stabilizer 770, or a combination of several of them.

[0043] The lubricant in the surface layer includes, but is not limited to, one or a combination of several of the following: low-density polyethylene wax, stearic acid amide, oleic acid amide, silicone oil, low-molecular fluorine resin (fluoroether oil), and pentaerythritol stearate PETS.

[0044] The dispersant in the surface layer includes, but is not limited to, one or a combination of several of the following: paraffin wax, polyethylene wax, barium stearate, and calcium stearate.

[0045] The compatibilizer of the core layer includes, but is not limited to, one selected from maleic anhydride graft copolymer, epoxy graft copolymer, GMA graft copolymer, terpolymer MBS or a combination of several thereof.

[0046] Manufacturing Example 1

[0047] The raw materials of the surface layer include, by mass, 92.7 parts of PBT, 5 parts of TPEE, 1 part of tetrafluoroethylene powder, 0.3 parts of fumed silica powder, 0.4 parts of antioxidant, 0.2 parts of anti-ultraviolet additive, 0.2 parts of lubricant, and 0.2 parts of dispersant; the above raw materials are stirred in a high-speed mixer for 8 minutes, and processed according to step S1 of the preparation method in the embodiment to obtain surface layer granules;

[0048] The raw materials of the core layer include, by mass, 20 parts of PC, 75 parts of PETG, and 5 parts of a maleic anhydride grafted compatibilizer; the raw materials are stirred in a high-speed mixer for 8 minutes, and processed according to step S2 of the preparation method in the embodiment to obtain core layer pellets;

[0049] Then, the polyester film is obtained according to step S3 of the preparation method in the embodiment; wherein the temperatures of the 6 heating sections of the first extruder are: 210°C, 240°C, 250°C, 250°C, 260°C, 260°C; the temperatures of the 6 heating sections of the second extruder are: 190°C, 210°C, 210°C, 210°C, 210°C, 210°C; the cooling temperature in step S3 is 60°C.

[0050] Manufacturing Example 2

[0051] The difference from Manufacturing Example 1 is that the raw materials of the surface layer include, by mass, 97.5 parts of PBT, 1.5 parts of tetrafluoroethylene powder, 0.4 parts of antioxidant, 0.2 parts of anti-ultraviolet additive, 0.2 parts of lubricant, and 0.2 parts of dispersant; the raw materials of the core layer include, by mass, 35 parts of PC, 62 parts of PETG, and 3 parts of terpolymer TP801 compatibilizer; the rest are the same as Manufacturing Example 1.

[0052] Manufacturing Example 3

[0053] The difference from Manufacturing Example 1 is that the raw materials of the surface layer include, by mass, 94 parts of PBT, 5 parts of fumed silica powder, 0.4 parts of antioxidant, 0.2 parts of anti-UV additive, 0.2 parts of lubricant, and 0.2 parts of dispersant; the raw materials of the core layer include, by mass, 40 parts of PC, 57 parts of PETG, and 3 parts of epoxy-grafted EVA compatibilizer; the rest are the same as Manufacturing Example 1.

[0054] Manufacturing Example 4

[0055] The difference from Manufacturing Example 1 is that the raw materials of the surface layer include, by mass, 98 parts of PBT, 1 part of tetrafluoroethylene powder, 0.4 parts of antioxidant, 0.2 parts of anti-ultraviolet additive, 0.2 parts of lubricant, and 0.2 parts of dispersant; the raw materials of the core layer include, by mass, 40 parts of PC, 58 parts of PETG, and 2 parts of terpolymer TP801 compatibilizer; the rest are the same as Manufacturing Example 1.

[0056] The above manufacturing examples 1 to 4 and the comparative example (95PBT+5 anti-wear agent) were tested, and the performance is shown in the following table:

[0057]

[0058] It should be noted that the characterization of the adhesion performance is: the width of the engraved groove that can be completely filled after the film is deformed under the heat sealing temperature condition. Usually, the fixed value of the groove depth is 0.2mm. The lower the heat deformation temperature and the smaller the groove width that can be filled, the better the adhesion performance.

[0059] From the performance tests in the above table, it can be clearly seen that the shrinkage rate of the films of Manufacturing Examples 1 to 4 is significantly reduced compared with the films of the comparative example; the lamination performance is significantly improved, and the heat sealing temperature is also significantly reduced; the surface hardness of the films of Manufacturing Examples 1 to 4 is all above 2H, the anti-scratch effect is excellent, the surface tension is not higher than 32 dyne / cm, and it has good wear resistance.

[0060] The above embodiments should not limit the present invention in any way, and any technical solutions obtained by equivalent replacement or equivalent conversion shall fall within the protection scope of the present invention.

Claims

1. A polyester film with low shrinkage, good adhesion and wear resistance, characterized in that: It comprises two surface layers and a core layer located between the two surface layers; the material of the surface layer is mainly composed of polybutylene terephthalate and abrasion resistant agent; the material of the core layer is mainly composed of a mixture of polycarbonate and polyethylene terephthalate-1,4-cyclohexanedimethanol; wherein, The surface layer material mainly consists of 80-99 parts of polybutylene terephthalate and 0.001-10 parts of anti-wear agent by mass; the anti-wear agent is one or a combination of tetrafluoroethylene powder and silicon dioxide powder; The core layer material mainly consists of 10-90 parts of polycarbonate and 10-90 parts of polyethylene terephthalate-1,4-cyclohexanedimethanol by weight; Thermoplastic polyester elastomer is also added into the surface layer material.

2. A method for preparing a polyester film with low shrinkage, good adhesion and wear resistance as claimed in claim 1, characterized in that: The preparation method is specifically carried out according to the following steps: S1, polybutylene terephthalate, anti-wear agent and other additives are mixed in a high-speed mixer, and then melt-blended, extruded and granulated by a twin-screw extruder to obtain surface layer pellets; S2, mixing polycarbonate, polyethylene terephthalate-1,4-cyclohexanedimethanol, and other additives in a high-speed mixer, and then melt-blending, extruding, and granulating through a twin-screw extruder to obtain core layer pellets; S3. Prepare a three-layer co-extrusion extruder consisting of two extruders, add the surface layer pellets to the first extruder, add the core layer pellets to the second extruder, the extruded melt enters and is compounded in the die head, and the compounded multi-layer melt is shaped, cooled, pulled, and annealed to obtain a polyester film.

3. The method for preparing a polyester film with low shrinkage, good adhesion and wear resistance according to claim 2, characterized in that: In step S1, the melt blending time of the twin-screw extruder is 2-10 min, the extrusion temperature is 190-240° C., and the screw speed is 15-80 r / min; in step S2, the melt blending time of the twin-screw extruder is 2-10 min, the extrusion temperature is 190-220° C., and the screw speed is 15-80 r / min.

4. The method for preparing a polyester film with low shrinkage, good adhesion and wear resistance according to claim 2, characterized in that: In step S3, the first extruder has a screw aspect ratio of 25-33, and comprises a barrel with 6 heating zones, and the barrel temperatures are set to: 220-270°C in the first zone, 230-280°C in the second zone, 230-280°C in the third zone, 230-280°C in the fourth zone, 230-280°C in the fifth zone, and 230-280°C in the sixth zone.

5. The method for preparing a polyester film with low shrinkage, good adhesion and wear resistance according to claim 2, characterized in that: In step S3, the second extruder has a screw aspect ratio of 25-33, and comprises a barrel with 6 heating zones, and the barrel temperatures are set to: 190-220°C in the first zone, 190-230°C in the second zone, 190-230°C in the third zone, 190-230°C in the fourth zone, 190-230°C in the fifth zone, and 190-230°C in the sixth zone.

6. The method for preparing a polyester film with low shrinkage, good adhesion and wear resistance according to claim 2, characterized in that: In step S3, the die head is a single-channel intracavity composite die head, and the temperature is set to 220-280°C.

Citation Information

Patent Citations

  • Rear surface protection sheet for solar cell module and solar cell module protected by such protection sheet

    CN101861657A

Cited By

  • Low-softening-point release film and preparation method thereof

    CN122211023A